Formation Mechanism and Governance Path of Social Exclusion of Agricultural Transfer Population in Demolition and Resettlement Areas - Sun, Chunling (International Journal of Social Sciences and Public Administration, 2024)
Citizenship of the agricultural transfer population is the primary task of new urbanisation, and is the path to achieving high-quality development and common prosperity in urban and rural areas. However, in the process of integrating into the city, the agricultural transfer population faces social exclusion, such as the coldness of the aborigines, difficulties in re-employment, limitations in access to resources, discrimination in rural culture, and poor identity. Based on the theory of social exclusion, this paper analyses the above attributes of social exclusion, such as relativity, dynamism and dynamics, and constructs a framework for analysing the mechanism of social exclusion of the agricultural transfer population in the resettlement area, which is based on the social relations, mode of living and cultural environment. It is argued that complex factors such as breakage of existing social relations and stalemate of new social relations, stripping away of farming mode and dependence on urban livelihood, difficulty in self-identification and lack of social identity, etc., have played a role in the social exclusion of the agricultural transfer population in the demolition and resettlement areas in the process of integrating into the city. To eliminate this kind of social exclusion, it is necessary to improve the supporting policies for demolition and resettlement, build a multicultural coexistence model, and promote two-way identity acceptance of the residents.